(untitled) (Huellas, 2026)
In this article, we seek to characterize the role of Río Cuarto in the reproduction of agricultural logic. Using an ontological approach associated with post-foundational thinking, in dialogue with related theoretical perspectives on territory, we reconstruct the territorial actions promoted and implemented in this city and its productivity in the relaunch of the accumulation model inherent in modern globalized agriculture. The article is structured in three analytical moments. First, we characterize the logic of agrobusiness, specifically highlighting the macrosocioterritorial implications that the structure has for its reproduction. Second, we identify the place of Río Cuarto in the spatial division of agrobusiness and its role in the relegitimation and non-relaunch of modern agriculture. Finally, in a third phase, we problematize the promise of plenitude associated with the imagination of the Silicon Valley.